Allah yang Mendengar: Telaah Naratif Kejadian 16:13 sebagai Dasar Etika Mendengar Guru dalam Pendidikan Agama Kristen - Elfin Warnius Waruwu Waruwu (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2026)
This article addresses a foundational problem in Christian Religious Education (CRE): the systematic neglect of students’ voices and lived experiences within pedagogical practice. Drawing on the narrative of Hagar in Genesis 16:13 specifically her naming of God as El-Roi (“the God who sees me”) this study constructs a theology of listening as a spiritual and pedagogical imperative. The research employs a qualitative approach utilizing narrative theology and ethical hermeneutics as its methodological framework, with Genesis 16:1–13 as the primary text and corroborated by secondary literature in narrative theology, pedagogical theory, and CRE studies. The analysis reveals that God’s act of hearing Hagar functions not merely as a biographical episode, but as a theological paradigm of divine solidarity with the marginalized. From this paradigm, a three-dimensional ethic of listening is constructed for CRE teachers: (1) active listening as spiritual hospitality that creates safe spaces; (2) dialogical presence that reconstitutes the teacher-student relationship on an I–Thou rather than I–It basis; and (3) prophetic listening as a liberating counter-practice against dehumanizing educational systems. The study concludes that the ethic of listening, grounded in the El-Roi theology, constitutes a prophetic vocation for Christian educators to teach not merely with cognitive expertise, but with a listening presence that honors the sacred dignity of each student.   Artikel ini mengangkat persoalan mendasar dalam Pendidikan Agama Kristen (PAK): pengabaian sistematis terhadap suara dan pengalaman hidup peserta didik dalam praktik pedagogis. Dengan bertolak dari narasi Hagar dalam Kejadian 16:13 khususnya penamaannya terhadap Allah sebagai El-Roi (“Allah yang melihat aku”) penelitian ini membangun teologi mendengar sebagai imperatif spiritual dan pedagogis. Penelitian menggunakan pendekatan kualitatif dengan teologi naratif dan hermeneutika etis sebagai kerangka metodologis, bersumber dari teks Kejadian 16:1–13 sebagai data primer dan literatur bidang teologi naratif, pedagogi, serta PAK sebagai data sekunder. Analisis menunjukkan bahwa tindakan Allah yang mendengar Hagar bukan sekadar episode biografis, melainkan paradigma teologis tentang solidaritas ilahi bagi yang termarginalisasi. Dari paradigma ini dibangun etika mendengar tiga dimensi bagi guru PAK: (1) mendengar aktif sebagai hospitalitas spiritual; (2) kehadiran dialogis yang merekonstruksi relasi guru-murid atas dasar Aku-Kamu; dan (3) mendengar profetik sebagai praktik liberatif. Penelitian menyimpulkan bahwa etika mendengar yang berakar pada teologi El-Roi merupakan panggilan profetik bagi guru Kristen untuk mengajar bukan sekadar dengan keahlian kognitif, tetapi dengan kehadiran mendengar yang menghormati martabat setiap murid.